A digital wide range neutron flux measuring system for HL-2A - 袁晨 吴军 阴泽杰 (Plasma science & technology, 2017)
To achieve wide-range, high-integration, and real-time performance on the neutron flux measurement on the HL-2A tokamak, a digital neutron flux measuring（DNFM） system based on the peripheral component interconnection（PCI） e Xtension for Instrumentation express（PXIe） bus was designed.This system comprises a charge-sensitive preamplifier and a field programmable gate array（FPGA）-based main electronics plug-in. The DNFM totally covers source-range and intermediate-range neutron flux measurements, and increases system integration by a large margin through joining the pulse-counting mode and Campbell mode. Meanwhile, the neutron flux estimation method based on pulse piling proportions is able to choose and switch measuring modes in accordance with current flux, and this ensures the accuracy of measurements when the neutron flux changes suddenly. It has been demonstrated by simulated signals that the DNFM enhances the full-scale measuring range up to 1.9×10^8cm^-2s^-1, with relative error below 6.1%. The DNFM has been verified to provide a high temporal sensitivity at 10 ms time intervals on a single fission chamber on HL-2A.